Critical Discourse Analysis of Bulhe Shah’s and Mast’s poetry - Naeem Dilpul (Linguistics and Literature Review, 2016)
This study attempts to capture the essence of two Sufi poets hailing from divergent origins, Baba Bulhe Shah from Punjab and Mast Twakalli from Balochistan to see their ways of preaching Sufism through their idiosyncratic ways. It also looks into their poetic narratives and underlying discourse embedded in them by analytically investigating the phenomena under study. The study is secondary in nature, so the data was collected from their books and then thorough study of their poetry was undertaken. The study in the process searched for common emerging patterns appearing in the poetry and their Sufi expressions.